The Practice of OTC Dispensing by Community Pharmacist in Nepal - Shakya, Sangita; Sedai, Susmita; Shakya, Ronas (Journal of Advanced Academic Research, 2021)
Over the counter (OTC) medications are the group of drugs that can be sold without the prescription of a registered medical practitioner to the consumers. Pharmacists are the most accessible health care professionals to the patient for the treatment of their minor illness. To provide appropriate advice to the patient at the time of dispensing and over-the-counter (OTC) medication counselling, community pharmacists need access to current and reliable information about medicines. A descriptive study was conducted on fifty pharmacists present in the community pharmacy of Kathmandu and Lalitpur districts. Predesigned validated questionnaire consisting of 16 questions were taken for the collection of data. Qualification of pharmacists, numbers of consumer asking for OTC medication in a week, most commonly dispensed OTC medicines by pharmacists, common symptoms told by consumers and average working hour of community pharmacists were recorded. The approval from the concerned authorities was taken. The study was a community based descriptive study done for 3 months. The data of the study was analyzed by using SPSS version 18. Out of 50 Pharmacists, 27 were males and 23 were females. Most of the study populations were qualified as assistant pharmacy. 82% of Community Pharmacy encountered more than ten consumers in a week. Analgesics and antipyretics, drugs for gastritis, antiprotozoals and antihistamines were the most commonly dispensed drugs by the pharmacies. The most common symptoms enquired by patients/consumers were fever (92%), common cold (90%) and headache (86%) as reported by pharmacists respectively. Average working hours of community pharmacists were 67 hours per week. Few pharmacists knew the meaning of terms related to evidence-based health. Most respondents agreed that pharmacists have the necessary training to prescribe. There is increasing use of OTC medicines in Nepal. The study on community pharmacy practices regarding over the counter medicines can assist in evaluating pattern of use of OTC medicines by consumers thus help to reduce abuse and misuse of such medicines.